Laser Powder Bed Fusion: tailoring the microstructure of alloys for biomedical applications. (2019) - Santecchia, E.; Mengucci, P.; Gatto, A.; Bassoli, E.; Denti, L.; Rutkowski, B.; Barucca, G.
Abstract: Additive manufacturing (AM) is particularly attractive for biomedical applications, where complex geometries and a high degree of individualization are required. Laser powder bed fusion (LPBF) is an AM technology exploiting the action of a solid-state laser to locally melt a metal powder according to a computer aided design (CAD) model. In the present study, the EOS Cobalt Chrome SP2 (Co-Cr-Mo-W) and Ti64 (Ti6Al4V) powders were sintered by the system equipped with a Yb fiber laser. During LPBF, the Co-Cr-Mo-W metal powder undergoes total melting followed by rapid cooling, giving rise to athermal martensitic phase transformation from the high-temperature γ (fcc) phase to the low-temperature ε (hcp) phase. This produces an intricate network of thin ε-lamellae inside the γ phase matrix. After the firing cycle this structure is maintained, and a massive presence of coarse precipitates is also observed. Owing to the rapid cooling taking place during LPBF, in Ti6Al4V sintered samples only the acicular martensitic α' phase is present. The firing cycle induces the β phase formation at the α plate boundaries and this microstructure leads to reduced values of strength, with respect to those of the as-sintered samples. The highlighted behaviors show that by tuning the post-production heat treatments it is possible to tailor the microstructure and the mechanical properties.